PROFIL LABORATORIUM IPA/BIOLOGI SMP SWASTA DI KOTA PEKANBARU - Mellisa Mellisa (Jurnal Pelita Pendidikan, 2018)
The method of this research is a survey which conducted to collect information carried out by compiling a list of questions submitted to respondents. Commonly, survey research is used to examine all a group or individual behavior. Collecting the data using observation and interview sheets. Data collection uses observation sheets based on Minister of National Education Regulation No.24 of 2007. The private junior high schools In Pekanbaru city, laboratory profile resulted in complete criteria on average based on the completeness of science and biology laboratory facilities and infrastructure at five private junior high schools. At Private Middle School of Dwi Sejahtera obtained a score of 55.88% (Complete). Furthermore, the percentage of Private Middle School of Bhayangkari was obtained at 77.4% (Very Complete). At Private Junior High School of Yabri, the percentage obtained was 53.58% (Complete) and Private Junior High School of Technology obtained a percentage of 1.42% (Very Incomplete), then Private Junior High School of Insan Utama obtained a percentage of 54% (Complete).Keywords: Laboratory Profile of Science / Biology, Teacher Competence of Laboratory